2005
DOI: 10.1021/ef050161u
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Probing of n-Alkane−Petroleum Asphaltene Interactions

Abstract: In this work, we report results of calorimetric studies on interactions between petroleum asphaltenes and n-alkanes. It was observed that mixing of n-alkanes with asphaltenes leads to exothermic thermal effects. This effect is irrespective of the asphaltene state and occurs either with precipitated asphaltenes or with solutions containing dissolved asphaltenes. This phenomenon is explained by a partial immobilization of n-alkanes in the protecting shell formed by aliphatic lateral chains of asphaltenes. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 14 publications
6
34
0
Order By: Relevance
“…This was explained by the partial dissolution of n-alkanes upon interacting with the lateral aliphatic chains of the asphaltenes; the almost solid nature of the partially immobilized alkanes caused the effect of wax nucleation and induced asphaltenes flocculation. 16 Similar results were found by other researchers. 17,18 Orea et al 19 studied asphaltenes from Furrial and Ayacucho crude oils to test retention of alkane compounds on asphaltenes.…”
Section: Introductionsupporting
confidence: 88%
“…This was explained by the partial dissolution of n-alkanes upon interacting with the lateral aliphatic chains of the asphaltenes; the almost solid nature of the partially immobilized alkanes caused the effect of wax nucleation and induced asphaltenes flocculation. 16 Similar results were found by other researchers. 17,18 Orea et al 19 studied asphaltenes from Furrial and Ayacucho crude oils to test retention of alkane compounds on asphaltenes.…”
Section: Introductionsupporting
confidence: 88%
“…A greater abundance of aliphatic chains in AsphIri asphaltenes permits a better interaction with the paraffins of the C24-C28 system promoting co-crystallization phenomena, where the asphaltenes are partially integrated to the crystal network and probably acting as nucleation sites, causing a slight increasing of WAT. Moreover, the partial immobilization of the paraffins engaged in the interactions with the asphaltene alkyl chains may promote a "quasicrystallization" phenomenon of the paraffins in the asphaltene network, such interaction results in exothermic effects as has been reported in literature [46,47], which explains the significant increasing of crystallization heat of the model system with AsphIri asphaltenes as observed in Table 4. On the other hand, the most aromatic asphaltenes (AsphPC) with a bigger and more condensed aromatic core and with a smaller amount of aliphatic substituents inhibit in some extent the paraffin-asphaltene interactions so that they cannot be incorporated to the paraffin crystal structure hindering nucleation process and crystal network growth, which results in a WAT decreasing with a lower crystallization enthalpy due to the formation of a disordered solid phase.…”
Section: Dsc Study Of the Effect Of Asphaltenes On Liquid-solid Phasementioning
confidence: 51%
“…Yang and Kilpatrick,41 concluded that there is no evidence for any intermolecular interaction between waxes and asphaltenes to suggest synergy in precipitation, so that only one between wax and asphaltene undergoes a phase change and precipitates, while the other one is just a portion of the crude oil occluded in the deposit. In contrast, Mahmoud et al45 observed that mixing of n ‐alkanes with asphaltenes leads to exothermic thermal effects irrespective of the asphaltene being already precipitated or dissolved. The phenomenon is attributed to a partial immobilization of n ‐alkanes in the protecting shell formed by aliphatic lateral chains of asphaltenes and validates the idea that n ‐alkanes contribute to both nucleation of the wax crystals and asphaltene flocculation.…”
Section: Introductionmentioning
confidence: 89%